Analysis of The Impact of Temperature and Discharge Current on The Efficiency of LiFePO4 Batteries in Solar Charging Stations - Winarno, Istiyo; Agung, Ach. Fathullah Pria; Dewantara, Belly Yan (Muhammadiyah University, Sidoarjo, 2024)
The demand for electrical energy is increasing, along with technological advancements and population growth. Many countries still rely on petroleum, coal, and aerosol gasoline, exacerbating global warming. Electric vehicles offer a promising solution to reduce greenhouse gas emissions and dependence on fossil fuels, although their primary challenge is the availability of charging infrastructure. Solar-powered electric motor charging stations can help reduce electricity demand and global warming. An efficient charging system is needed to analyse the impact of temperature and discharge current on the energy produced to achieve this. Several load tests and temperature measurements over 5 days were conducted to cluster temperatures occurring throughout a full day. The tests using data acquisition showed energy losses caused by the effect of temperature on the charging station's storage battery. Energy efficiency graphs for each test case indicated a varied decrease in energy efficiency, with higher efficiency at lower temperatures and smaller energy losses compared to other temperatures. The load amount also affects the magnitude of energy losses. At a 500W load, the average energy loss was 46Wh, while at a 1000W load, the average energy loss was 52Wh per hour of testing the storage battery discharge. In summary, temperature and load amount can affect energy efficiency and the resulting losses.